Conformal screen on lightlike hypersurfaces. - DUGGAL, Krishan Lal; ATINDOGBE, COMLAN CYRIAQUE; DUGGAL, Krishan Lal (My University, 2004)
We study some properties of a lightlike hypersurface M , of a Lorentzian manifold, whose shape operator is conformal to the shape operator of its screen distribution. We prove that some specified aspects of the null geometry of M reduce to the Riemannian geometry of a leaf of its screen distri- bution. As a physical relevance, we show that there exists such a class of screen globally conformal lightlike hypersurfaces of 4-dimensional stationary non-flat spacetimes which admit a Killing horizon.
Keywords: lightlike hypersurface; conformal screen; stationary spacetime